The Effectiveness of English Organization (ESC) to Improve Speaking Skill of Students at Hamzanwadi University - Muhammad Khairunnasri; Purna Hijjah; Sri Herawati; Septi Andriana; Selamet Riadi Jaelani (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
This research aimed to examine the effectiveness of the English Speaking Club (ESC) organization in enhancing students' speaking skill at Hamzanwadi University. A qualitative method was adopted for the study, with ten ESC members from various programs and semester levels serving as the subjects. Data was collected through a questionnaire distributed via Google Form. The results of this study indicated that the ESC organization effectively assisted students in improving their speaking skills, including pronunciation, vocabularies, fluency, and self-confidence.